Parkin Regulation and Neurodegenerative Disorders - Zhang, Cheng-Wu; Hang, Liting; Yao, Tso-Pang; Lim, Kah-Leong (Frontiers in Aging Neuroscience, 2016)
Parkin is a unique, multifunctional ubiquitin ligase whose various roles in the cell, particularly in neurons, are widely thought to be protective. The pivotal role that Parkin plays in maintaining neuronal survival is underscored by our current recognition that Parkin dysfunction represents not only a predominant cause of familial parkinsonism but also a formal risk factor for the more common, sporadic form of Parkinson’s disease. Accordingly, keen research on Parkin over the past decade has led to an explosion of knowledge regarding its physiological roles and its relevance to PD. However, our understanding of Parkin is far from being complete. Indeed, surprises emerge from time to time that compel us to constantly update the paradigm of Parkin function. For example, we now know that Parkin’s function is not confined to mere housekeeping protein quality control roles but also includes mitochondrial homeostasis and stress-related signalling. Furthermore, emerging evidence also suggest a role for Parkin in several other major neurodegenerative diseases including Alzheimer’s disease and Amyotrophic Lateral Sclerosis. Yet, it remains truly amazing to note that a single enzyme could serve such multitude of functions and cellular roles. Clearly, its activity has to be tightly regulated. In this review, we shall discuss this and how dysregulated Parkin function may precipitate neuronal demise in various neurodegenerative disorders.